2008
DOI: 10.1108/09565690810916410
|View full text |Cite
|
Sign up to set email alerts
|

The development of records management at the European Central Bank

Abstract: PurposeThe purpose of this paper is to provide background to the other papers in this issue of the Records Management Journal.Design/methodology/approachThe information in this paper is based on the author's own experience and discussions with colleagues with direct experience of the events described.FindingsThe European Central Bank's approach to building capacity in records management, by appointing in‐house staff and investing in professional training and qualifications and fully integrating records managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…The problems identified in this study were similar to those identified in studies that were conducted elsewhere. For instance the findings confirm what Katundu (2002), Mnjama (2004), Ndenje-Sichalwe et al 2011, Orr (2008) and Shepherd and Yeo (2003) Chief Archivist 2 mentioned such problems as:…”
Section: Records Management Problemssupporting
confidence: 64%
See 1 more Smart Citation
“…The problems identified in this study were similar to those identified in studies that were conducted elsewhere. For instance the findings confirm what Katundu (2002), Mnjama (2004), Ndenje-Sichalwe et al 2011, Orr (2008) and Shepherd and Yeo (2003) Chief Archivist 2 mentioned such problems as:…”
Section: Records Management Problemssupporting
confidence: 64%
“…Extant literature (Katundu, 2002;Luyombya and Bukirwa, 2013;Mnjama, 2004;Ndenje-Sichalwe et al, 2011;Okello-Obura, 2012;Orr, 2008;Shepherd and Yeo, 2003) has indicated that there are still a lot of records management problems in both private and public organisations. Such problems can be addressed through recruiting professional records managers or engaging consultancy services.…”
Section: Records Management Challenges In Zimbabwementioning
confidence: 99%
“…If records management is implemented properly within the organization, various benefits, such as enhancement of service delivery, quick decision-making and compliance with archival legislation, can be realized (Shepherd 2006:7). This was shown by Orr (2008:167) when indicating the benefits realized by the European Central Bank in implementing a centralized records management model that was suitable for the organization and had a dedicated records management section. Mcleod (2012:187) suggests that it is advisable to manage records in a hybrid environment to benefit from both paper and electronic media.…”
Section: Types Of Records Management Modelsmentioning
confidence: 98%
“…Again working with staff colleagues and helping them all to fulfil their record keeping duties will raise the profile and potentially increase the influence of the records manager. The setting up of a professional development programme and career structure for records personnel is only possible in a small number of organisations although there are a number of examples across the sectors (BBC (Hare and McLeod, 2001), European Central Bank (Orr (2008)) from which models can be drawn.…”
Section: A Message For Allmentioning
confidence: 99%